Religious Tolerance in the Light of Seerah Prophet and his Companions Teachings - Hafsa Qadir Buzdar; Abdul Qadir Buzdar; Muhammad Ismail (Pakistan Journal of Islamic Research)
Based upon reviews and previous empirical research which lacks tolerance environment. This research article highlights the importance of religious tolerance in our society. This paper analyses the significance of the tolerance through different example events and references, in the light of Holy life of Hazrat Muhammad (Peace be Upon Him). It we define tolerance, such as tolerance is a name to bear hand ship in pain, we also give different substitute rather or explanation of tolerance. In substitute words, if tolerance means punishment, it will not be suitable vaster we can say that it is act to compel someone for good. Further it has been stated religious tolerance in the light teaching of Islam. In which the significance of tolerance is elaborated through different Ayyats (Verses), along with the past religious events of Sahaba and Prophets, by Prominent Muslim Scholar. Similarly when we look at the life of Hazrat Muhammad (Peace be upon him), on different occasion how He (Peace be upon him) shows tolerance even he himself was in trouble and now He tolerate with Non-Muslims when they are very harsh to him, through different events in the life of Holy Prophet (PBUH), he gives us a complete code of life as tolerance with Jews gives us, inspiration to lead our life by following to the teaching of Holy Prophet’s life practically through tolerance.